Method for testing thickness of oxide layer on surface of micron-sized boron particle
By preparing boron particle slices through focusing ion beams and combining transmission electron microscopy and energy dispersion X-ray spectroscopy, the problem of the existing technology being difficult to accurately characterize the thickness of boron particles is solved, and high-precision oxide layer determination is achieved, which improves the ignition technology. Reliability and safety of the agent.
Patent Information
- Application Number
- CN202411297983.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to accurately characterize the thickness of the surface oxide layer of micron-scale boron particles, and traditional methods cannot effectively evaluate the performance of boron potassium nitrate ignition powder, which affects the reliability and safety of ignition agents.
Boron particle slices were prepared by focusing ion beam micro-nano processing technology, and the oxide layer on the slice was morphologically and energy spectrum characterized by transmission electron microscopy and energy dispersion X-ray spectroscopy to obtain the thickness of the boron particle oxide shell layer.
The precise determination of the thickness of the surface oxide layer of micron-scale boron particles is achieved, and it has the advantages of high sample preparation success rate, high characterization accuracy and high accuracy, which helps to evaluate the performance of boron potassium nitrate ignition powder.
Smart Images

Figure CN119437104A_ABST
Abstract
Description
[0001] Technical field: The present invention relates to the field of detection technology, and provides a method for testing the thickness of an oxide layer on the surface of micron-sized boron particles. Background Art
[0002] Boron potassium nitrate ignition powder is one of the commonly used pyrotechnic agents. Boron powder is an important component of boron potassium nitrate ignition powder and has a key influence on the performance of boron potassium nitrate ignition powder. During storage, boron powder will react with oxygen, water molecules, etc. in the air to form an oxide layer on the surface of boron particles. The formation of the oxide layer affects the energy transfer efficiency of the ignition process, resulting in a reduction in the boron content of the system, which directly leads to a reduction in the reliability and safety of the pyrotechnic agent. Therefore, characterizing the oxide layer on the surface of boron particles is helpful to evaluate the performance of boron potassium nitrate ignition powder and has received widespread attention in recent years.
[0003] Boron powder is generally in an amorphous state, and its morphology is close to that of agglomerated small boron particles. The scale of the oxide layer of boron particles is usually at the nanometer level, which brings difficulties to the accurate characterization of the oxide layer of boron particles. Traditional characterization methods such as scanning electron microscopy can only characterize the morphology of the surface of boron particles, but cannot characterize the internal structure; transmission electron microscopy can characterize the internal structure of objects, but is greatly affected by particle size, agglomeration state, etc.; theoretically, by preparing boron particle transmission samples through focused ion beam, combined with transmission electron microscopy and energy spectrum analysis, micro-nano structures such as oxide shells can be characterized, but the texture of boron particles is relatively soft, and slices may be damaged under ion beam cutting. In summary, based on focused ion beam micro-nano processing technology and optimizing the thinning method, the thickness of the oxide layer on the surface of micron-level boron particles can be measured. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and propose a testing method for the thickness of the oxide layer on the surface of micron-sized boron particles. Boron particle slices are prepared by focused ion beam micro-nano processing technology, and then the slices are selected and thinned to obtain a cross-section of the boron particles. The oxide layer contained on the slices is characterized in morphology and energy spectrum using a transmission electron microscope and an energy dispersive X-ray spectrum to obtain the thickness of the oxide shell of the boron particles. This method is an effective method for studying the internal micro-nano structure of the oxide layer of the boron particles, and has the advantages of high sample preparation success rate, high characterization accuracy, and high characterization precision.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] The present invention aims to provide a method for testing the thickness of the oxide layer on the surface of micron-sized boron particles, the method comprising the following steps:
[0007] Step 1: Preparation of micron-sized boron particles: Disperse the micron-sized boron particles on the surface of the conductive tape, use compressed air to spray the conductive tape to ensure that the boron particles are firmly adhered, and then place the conductive tape in the ion beam vacuum chamber and evacuate it;
[0008] Step 2: Preparation of transmission samples of micron-sized boron particles: deposit a Pt protective layer on the surface of the boron particles through a gas injection system to protect the oxide layer on the surface of the boron particles; use a focused ion beam to cut the boron particles to obtain boron particle slices; use a manipulator to fix the boron particle slices to a copper mesh; use a gas injection system to selectively thin the boron particle slices to meet the requirements of the transmission electron microscope while ensuring mechanical strength, and complete the preparation of the boron particle transmission sample.
[0009] Step 3: Transmission characterization of micron-sized boron particles: Place the transmission sample of the boron particles into a transmission electron microscope, characterize the boron particles through the transmission electron microscope, and test the thickness of the oxide layer of the boron particles.
[0010] Compared with the prior art, the present invention has the following advantages and effects:
[0011] 1. The present invention provides a method for testing the thickness of the oxide layer on the surface of micron-sized boron particles, which has broad application prospects in the fields of national defense, energetic materials, chemistry, etc. The testing steps include cutting the boron particles with a focused ion beam to obtain slices containing the oxidized shell structure of the boron particles, and performing morphological characterization and energy spectrum analysis on the oxide layer on the boron particle slices by transmission electron microscopy and energy dispersive X-ray spectroscopy, which has the advantages of intuitive, accurate and high-precision characterization results.
[0012] 2. The present invention provides a method for testing the thickness of the oxide layer on the surface of micron-sized boron particles. Before using a focused ion beam to cut the boron particles, a Pt metal layer is deposited on the surface of the boron particles through a gas injection system, thereby effectively protecting the structure of the oxide layer of the boron particles and ensuring the accuracy and precision of the characterization results.
[0013] 3. The present invention provides a method for testing the thickness of the oxide layer on the surface of micron-sized boron particles. The testing process involves using a focused ion beam to thin the boron particle slices. Different thinning methods should be adopted according to the different internal states of the boron particles: selective thinning is adopted for particles with loose internal structures to ensure the mechanical strength of the slices and improve the success rate of sample preparation; overall thinning is adopted for particles with stable internal structures to ensure the uniformity of the slices. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The operation flow chart of characterizing the oxidation shell layer on the surface of boron particles provided in Example 1 of the present invention;
[0015] Figure 2(a) SEM image of a boron particle sample provided in Example 1 of the present invention, and (b) SEM image of a boron particle surface after a Pt metal layer is deposited;
[0016] Figure 3 (a) A vertical cutting diagram of a focused ion beam in the front area of a particle, and (b) A vertical cutting diagram of a focused ion beam in the back area of a particle provided in Example 1 of the present invention;
[0017] Figure 4 (a) The welding diagram of the nanomanipulator and the boron particle slice provided in Example 1 of the present invention, and (b) The nanomanipulator transfers the boron particle slice;
[0018] Figure 5 The copper mesh image of boron particle slice alignment during the process of characterizing the surface oxidation shell of boron particles provided in Example 1 of the present invention;
[0019] Figure 6 (a) a selected thinning image of a boron particle slice provided in Example 1 of the present invention, and (b) an enlarged scanning electron microscope image of the thinning area;
[0020] Figure 7 (a) Transmission electron microscope image of a boron particle slice, (b) dark field image of the slice, and element line scan area provided for Example 1 of the present invention, including (c) boron element distribution and (d) oxygen element distribution.
[0021] Figure 8 This is a scanning electron microscope image of a boron particle sample provided in Example 2 of the present invention;
[0022] Fig. 9 (a) A vertical cutting diagram of a focused ion beam in the front area of a particle, and (b) A vertical cutting diagram of a focused ion beam in the back area of a particle provided in Example 2 of the present invention;
[0023] Fig.10 (a) A top view of a boron particle slice provided in Example 2 of the present invention, and (b) a slice view of a boron particle welded by a nanomanipulator;
[0024] Fig.11 (a) boron particle slice alignment copper mesh image and (b) boron particle slice selection thinning image provided for Example 2 of the present invention;
[0025] Fig.12 (a) boron particle slice transmission electron microscopy area 1, (b) boron particle slice transmission electron microscopy area 2 provided in Example 2 of the present invention;
[0026] Fig.13Provided in Example 2 of the present invention are (a) a dark field image and line scan position of region 1 of a boron particle slice, (b) corresponding line scan results of the boron element, (c) corresponding line scan results of the oxygen element, (d) a dark field image and line scan position of region 2 of a boron particle slice, (e) corresponding line scan results of the boron element, and (f) corresponding line scan results of the oxygen element.
[0027] Fig.14 The results of 10 measurements of the oxide shell on the surface of the boron particles provided in Example 1 of the present invention and their average values and standard deviations.
[0028] Fig.15 The results of 10 measurements of the oxide shell layer on the surface of region 1 of the boron particles provided in Example 2 of the present invention, as well as their average values and standard deviations.
[0029] Fig.16 The results of 10 measurements of the oxide shell layer on the surface of the boron particle region 2 provided in Example 2 of the present invention, as well as their average values and standard deviations. DETAILED DESCRIPTION
[0030] The present invention is implemented through the following embodiments, but the conditions and results described in the implementation do not limit the content and rights of the invention.
[0031] Embodiment 1:
[0032] 1. Sample preparation
[0033] Stick conductive tape on the FIB sample stage, take about 10 mg of the sample to be tested and place it on the filter paper. Use tweezers or toothpicks to stick the sample to the conductive tape. Be careful not to stick too much, 1-2 grains will be enough. Then use an ear bulb or compressed air to spray the sample on the conductive tape to ensure that the sample is firmly attached. Then put the sample that needs to be prepared by transmission into the FIB instrument cabin, evacuate the vacuum, and start the FIB dual-beam scanning electron microscope.
[0034] 2. Focused Ion Beam Sectioning
[0035] Select particles suitable for sample preparation in the field of view of the FIB instrument. Usually, the particle size should not be too small (the particle size should be kept between 100nm and 50μm to ensure the processing accuracy of the FIB), the particle should have a certain regular shape, and the particle should have a certain structural strength (the particle gaps should not be too many to ensure the structural strength) to prevent the particle surface from being damaged by the ion beam during the subsequent sample preparation process; Figure 2 (a) Particles with a width of about 10 μm. Adjust the particle angle so that the ion beam is perpendicular to the upper surface of the particle, determine the etching position, and retain Figure 2 For the sample in the red rectangle in (a), a Pt protective layer is plated on the upper surface of the slice that needs to be protected using the FIB gas injection function to prevent the ion beam from damaging the slice during the subsequent etching process. Figure 2(b) is a 52° oblique view of a boron particle. It can be seen that a layer of material with a smooth surface and a specific shape exists in part of the upper surface of the particle, indicating that Pt has been successfully deposited on the upper surface of the particle.
[0036] The FIB etching current and voltage were adjusted to perform ion beam etching on the portion other than the Pt coating to obtain boron particle slices. Figure 3 (a) The picture shows the front part of the boron particle after etching. Since the ion beam sputters vertically from top to bottom, a pit is formed on the conductive tape at the bottom of the particle; Figure 3 (b) is similar. After the position of the boron particle is rotated 180°, the back of the boron particle is etched with an ion beam to obtain a slice of the middle part of the boron particle. The slice thickness is about 1 μm. It can be seen from the figure that the internal structure of the boron particle is relatively loose. Continuing to etch and thin the slice may cause the slice to be damaged. Therefore, it is chosen to transfer the slice to a transmission copper mesh before further thinning.
[0037] Use a manipulator to take out the boron particle slice: first, use an ion beam to thin the end of the manipulator to make its size match the size of the boron particle slice; adjust the spatial position of the manipulator so that its end is close to the upper right corner of the boron particle slice, and place the manipulator close to the boron particle slice; perform gas deposition at the position where the manipulator contacts the boron particle slice, and use Pt coating to connect the manipulator and the boron particle slice, such as Figure 4 As shown in (a), the red frame position is the contact position between the manipulator and the boron particle slice, which is plated with a Pt layer; the ion beam etching operation is performed on the connection position between the boron particle slice and the bottom conductive tape to separate the boron particle slice from the bottom conductive tape, and the boron particle slice is taken out under the operation of the manipulator, as shown in FIG. Figure 4 (b) as shown.
[0038] After the boron particle slices are taken out by the manipulator, the spatial position of the manipulator is adjusted to align the boron particle slices with the notch of the transmission copper mesh (needs to be placed on the V-shaped column of the transmission copper mesh). Figure 5 As shown; a gas deposition operation is performed at a position close to the boron particles and the transmissive copper mesh, and a Pt layer is plated to connect the boron particle slice and the transmissive copper mesh (one on each side); then an ion beam etching operation is used to separate the robotic arm and the boron particle slice, and the robotic arm is withdrawn.
[0039] After the boron particle slices are fixed to the transmission copper mesh using ion beam deposition, the boron particle slices need to be thinned because the thickness of the boron particle slices is about 1μm, which is much larger than the 100nm required by the transmission electron microscope. The picture shows that there are many pores on the boron particle slices, indicating that its mechanical structure strength is low. If the entire boron particle slice is thinned, the boron particles may be destroyed under ion beam sputtering and the slices are "broken up". Therefore, it is necessary to select and thin the boron particle slices; select the right area of the slice for thinning, use a smaller current for the thinning operation, and perform multiple thinning operations. As the slice thickness decreases, the thinning current decreases successively, and finally obtain Figure 6 (a) shows a section of a boron particle. Figure 6 (b) The thin area in the red frame is the thinned boron particle slice. Since the thicker area on the left side of the slice is retained, the mechanical strength of the boron particle slice can be guaranteed to a certain extent, preventing the boron particle slice from being damaged during the transfer process from the FIB instrument to the TEM instrument.
[0040] 3. Characterization of slice oxide layer
[0041] The boron particles prepared in Example 1 were sliced and characterized by TEM. After FIB sample preparation, the internal structure of the boron particles was intuitively and clearly displayed on the TEM image, as shown in Figure 1. Figure 7 (a) is shown. The TEM image shows that the color inside the particle is lighter than the surface of the particle, and the surface of the particle is evenly covered with a layer of dark material. The content of dark material in different parts is different. It is considered that this layer of material is the oxide shell layer on the surface of the boron particle. In order to further determine the elemental composition of this layer of material, a dark field image of this area was obtained using TEM. Figure 7 (b) shows that under the dark field image, the black area on the surface of the boron particle is scanned by EDX line scanning. The scanning results are as follows: Figure 7 (c) and Figure 7 (d) As shown in the scanning results, the red image is the boron element counting peak, and the green image is the oxygen element counting peak. By comparing the two, it can be found that in some areas, when the oxygen element count is high, the boron element count is low. Combining the oxygen and boron element counts and the corresponding dark field image of the boron particle slice, it is proved that the white area covered on the surface of the boron particle slice in the dark field image is the boron particle oxidation shell area.
[0042] The transmission image of the boron particle slice was analyzed by TEM image processing software, and the oxide layer area in the image was measured using the measurement tool provided by the software. The same oxide layer area was measured 10 times, and the average value of the 10 measurements was taken as the thickness of the oxide layer in the area. The standard deviation was taken as the measurement error. The oxide layer thickness was 63.48nm, and the single measurement error was 1.49nm.
[0043] Embodiment 2:
[0044] 1. Sample preparation
[0045] Paste conductive tape on the FIB sample stage, take about 10 mg of the sample to be tested and place it on the filter paper, use tweezers or toothpicks to stick the sample to the conductive tape, then use an ear bulb or compressed air to spray the sample on the conductive tape to ensure that the sample is firmly adhered; then put the sample that needs to be prepared by transmission into the FIB instrument cabin, evacuate the vacuum, and start the FIB dual-beam scanning electron microscope.
[0046] 2. Focused Ion Beam Sectioning
[0047] Select the particles suitable for sample preparation in the FIB instrument field of view and select Figure 8 The particles shown are in agglomerated state, with a particle size of 70 to 80 μm. The particle angle is adjusted so that the ion beam is perpendicular to the upper surface of the particle, and the etching position is determined to retain Figure 8 For the sample in the red rectangular frame, a Pt protective layer is plated on the area in the red rectangular frame using the FIB gas injection function to prevent the ion beam from damaging the slice during the subsequent etching process.
[0048] The FIB etching current and voltage were adjusted to perform ion beam etching on the portion other than the Pt coating to obtain a slice inside the boron particle. Fig. 9 The two figures are scanning electron microscope images of the boron particle etching process. After the etching is completed, a slice of the middle part of the boron particle is obtained, and the slice thickness is about 5.64μm. It can be seen from the figure that the internal structure of the boron particle is relatively loose. Continuing to etch and thin the slice may cause the slice to be damaged. Therefore, it is chosen to transfer the slice to the transmission copper mesh before further thinning.
[0049] Use a robot to slice and remove the boron particles, such as Fig.10 As shown, the slice is subsequently aligned with the transmission copper mesh by a robot, and the two are connected using an ion implantation system, as shown in FIG. Fig.11 (a) After the boron particle slices are fixed to the transmission copper mesh using ion beam deposition, the boron particle slices need to be thinned because the thickness is about 5.64μm, which is much larger than the 100nm required by the transmission electron microscope. Fig.11 (b) The thinning process is performed on the portion of the slice within the red rectangle. A smaller current is used for the thinning process. Multiple thinning processes are performed. As the slice thickness decreases, the thinning current decreases. Finally, Fig.11 (b) The boron particle section shown was used for characterization.
[0050] 3. Characterization of slice oxide layer
[0051] The boron particles prepared in Example 2 were sliced and characterized by TEM. After FIB sample preparation, the internal structure of the boron particles was intuitively and clearly displayed on the TEM image, as shown in Figure 2. Fig.12The two images shown in (a) and (b) represent two different regions. The TEM image shows that the color inside the particle is lighter than the surface of the particle, and the surface of the particle is evenly covered with a layer of dark material. The content of dark material in different parts is different. It is considered that this layer of material is the oxide shell layer on the surface of the boron particle. In order to further determine the elemental composition of this layer of material, the dark field image of the two regions was obtained using TEM. Fig.13 As shown in (a) and (d), EDX line scans are performed along the orange line direction. The red image in the scan results is the boron element count peak, and the green image is the oxygen element count peak. By comparing the two, it can be found that there are some areas where the oxygen element count is high and the boron element count is low. Combining the oxygen and boron element counts and the corresponding dark field image of the boron particle slice, it is proved that the white area covered on the surface of the boron particle slice in the dark field image is the boron particle oxidation shell area.
[0052] The transmission image of the boron particle slice was analyzed by TEM image processing software. The oxide layer area in the image was measured using the measurement tool provided by the software. The same oxide layer area was measured 10 times. The average value of the 10 measurements was taken as the thickness of the oxide layer in the area, and the standard deviation was taken as the measurement error. The area 1 ( Fig.12 a) The oxide layer thickness is 79.92nm, and the thickness standard deviation is 8.80nm; region 2 ( Fig.12 b) The thickness of the oxide layer is 98.28 nm, and the standard deviation of the thickness is 9.29 nm. This method achieves accurate characterization of the oxide layer of boron particles, and has the advantages of intuitive, accurate and high precision results.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for testing the thickness of the oxide layer on the surface of micron-sized boron particles, characterized in that: The following steps are involved: Step 1: Preparation of micron-sized boron particles: Disperse the micron-sized boron particles on the surface of the conductive tape, use compressed air to spray the conductive tape to ensure that the boron particles are firmly adhered, and then place the conductive tape in the ion beam vacuum chamber and evacuate it; Step 2: Preparation of transmission samples of micron-sized boron particles: deposit a Pt protective layer on the surface of the boron particles through a gas injection system to protect the oxide layer of the boron particles; use a focused ion beam to cut the boron particles to obtain boron particle slices containing the oxide layer; use a manipulator to fix the boron particle slices to a copper mesh; use a gas injection system to perform selective thinning on the boron particle slices to meet the requirements of the transmission electron microscope while ensuring mechanical strength, thereby completing the preparation of the boron particle transmission sample. Step 3: Transmission characterization of micron-sized boron particles: Place the transmission sample of the boron particles into a transmission electron microscope, characterize the boron particles through the transmission electron microscope, and test the thickness of the oxide layer of the boron particles.
2. The method for testing the thickness of the oxide layer on the surface of micron-sized boron particles according to claim 1, characterized in that: In step 1, the particle size of micron-sized boron particles is required to be 100nm-50μm. If the particle size is too small, the etching accuracy of the focused ion beam cannot be guaranteed; if the particle size is too large, it indicates that the boron particles may be agglomerated by small particles, and the particles may be dispersed by the ion beam during the ion beam etching process.
3. The method for testing the thickness of the oxide layer on the surface of micron-sized boron particles according to claim 1, characterized in that: In step 2, a Pt metal layer is first deposited on the surface of a single boron particle by a gas injection system to protect the surface of the boron particle; the boron particle is cut by a Ga ion beam in a direction perpendicular to the surface of the conductive tape to obtain a boron particle slice, wherein the two cut sides of the slice are perpendicular to the surface of the conductive tape and parallel to each other, and the thickness is 0.5-1 μm; the end of the manipulator is gently brought close to the boron particle slice by a manipulator system, a Pt metal layer is deposited at the contact position between the two using a gas injection system, the end of the manipulator and the boron particle slice are fixed, and the bonding position of the boron particle and the conductive tape is cut by a Ga ion beam perpendicular to the cross section of the boron particle to separate the boron particle and the conductive tape; the manipulator is moved to transfer the boron particle slice from the conductive tape area to the transmission copper mesh area, and the bottom of the boron particle slice is aligned with the top of the transmission copper mesh and brought close to each other; A Pt metal layer is deposited at the contact position between the boron particle slice and the transmissive copper mesh using a gas injection system to connect the boron particle slice and the transmissive copper mesh; The two side planes of the boron particle slice are selectively cut by the Ga ion beam in a direction parallel to the two side planes, so that part of the side plane area is thinned, and the final thinning thickness is about 100-200nm, completing the preparation of the boron particle transmission sample.
4. The method for testing the thickness of the oxide layer on the surface of micron-sized boron particles according to claim 1, characterized in that: In step three, the morphology of the boron particle slices is characterized, and the oxide layer area is preliminarily judged by the difference in image contrast and lattice arrangement. The oxide layer area is scanned by energy spectrum line scanning using TEM dark field and energy dispersive X-ray spectroscopy. The scanning direction starts from the inside of the thin area of the boron particle slice, perpendicular to the oxide shell of the boron particle to the Pt metal layer deposition area outside the boron particle. The oxide shell structure of the boron particle is calculated using the change curves of the B and O elements combined with the TEM transmission image.
Citation Information
Cited By
Hydrophobic micro-nano flexible film structure and characterization method
CN120651156A